Designing a Human Resources Performance System in a Company Using the Analytical Hierarchy Process (AHP) Method - Heru Winarno; Syamsudin; Ade Riezky (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2023)
PT Melinia Nusa Wisata is a company engaged in the field of travel tourism services. As a result of problems from the human factor, namely delays in attendance in the field, the company's scheduled travel departures are inappropriate. This study aims to analyze how to improve the human resource performance system from the three criteria and three alternatives by using the Analytical Hierarchy Process (AHP) method with the help of Expert Choice software. The nature of this research is qualitative descriptive and exploratory research. The results of the study obtained the weight of each criterion, namely on work motivation by 26.6%, work discipline by 24.4%, work skills by 46%, and the alternative is an increase in welfare by 21.6%, an increase in human resource training 44.7%, an increase in facilities 33.7%. These results identify the highest weight, namely work skills and human resource training improvement, meaning that to improve the human resource performance system, the two highest criteria require special attention in their implementation.